PENERAPAN MODEL DISCOVERY LEARNING BERBASIS PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN PARTISIPASI BELAJAR - Ai Tin Sumartini (Institut Pendidikan Indonesia, 2022)
The current learning process needs to develop all the potential of students in terms of attitudes, knowledge and skills, so that they are expected to be able to participate in facing various demands of the times in social, national and state life. In reality, there are still many monotonous learning processes found, lack of student learning participation which has implications for the low learning outcomes obtained. This research aims to determine the application of the cooperative-based Discovery Learning Model in increasing student learning participation. The Discovery Learning model is one of the models developed in 21st century learning. Because with a scientific approach students are trained to observe various stimuli, identify problems, search for information themselves, process information, prove information through presentations and formulate generalizations or conclusions. This research method uses the Classroom Action Research method with the Lewin model which is carried out in two cycles, describing the process of implementing the cooperative-based Discovery Learning model in increasing student learning participation. The research results show that the cooperative-based Discovery Learning Model can increase student learning participation both individually and in groups from cycle I to cycle II. Likewise, the average posttest score increased from cycle I to cycle II. This has implications for improving learning outcomes.